Monitoring the occurrence of PAHs in Irish wastewater effluent - Jones, L.; Kinsella, Brian; Furey, A.; Regan, F. (Royal Society of Chemistry, 2012)
Polycyclic aromatic hydrocarbons (PAHs) are commonly occurring environmental pollutants, 8 of which have been chosen from the list of priority substances in the EU Water Framework Directive (WFD). The levels of PAHs in the environment are affected by a number of emission factors including anthropogenic activities, population equivalents, and weather, all of which must be taken into account when monitoring levels of PAHs being released into the environment via waste water treatment plant effluent. Effluent samples have been collected from nine different wastewater treatment plants in 2 areas of Ireland (Dublin and Cork) over a period of 3 years (2009-2011), including several weeks of high intensity sampling. Solid phase extraction is used in the sample preparation process with subsequent analysis by gas chromatography with mass spectrometric detection (GCMS). All samples analysed contained the priority PAHs in this study; however levels detected do not exceed environmental quality standards (EQSs). Herein these results are related to a number of key emission factors affecting the levels of PAHs present in wastewater treatment plant effluent. This study aims to complement storm water studies and inform future targeted priority substance monitoring programmes. Â© The Royal Society of Chemistry 2012.